The Dominant Discourse on the Economic Conjuncture and the Role of Economic Journalists - de Sousa, Antonio Paulino (Pontifícia Universidade Católica de São Paulo, 2015)
Macroeconomic forecasts are important activities for economic actors and economic and financial decisions are based on conjunctural analyses. Employing economic sociology, I analyze the role of economic journalists in the production of an ideological discourse on economic conjunctures. The dominant discourse of economists, or conjoncturalistes, has a social forcetied to “scientific” authority. But the efficacy of these discourses is  associated with the role exercised by economic journalists, whose arguments are based on official texts analyzing the international economic conjuncture. The construction of the space of economic journalists consists of identifying the power that they exert in the diffusion of the dominant ideas defended by the economic agents that dominate the material and symbolic spheres of  production.